Money and macroeconomics from first principles, for Elon Musk and other engineers - Keen, Steve, 1953-; Barbalich, Nick ([Spojené státy americké] : [nakladatel není známý], 2025)
This book applies engineering-style first principles thinking to economics, and reaches radically different conclusions about the economy to those that Musk has put forward, either when he reasons by analogy, or when he channels the thoughts of mainstream economists like Milton Friedman. If you want to understand money and macroeconomics, then this book is for you. It explains money creation using the fundamental laws of accounting, and derives macroeconomics directly from macroeconomic definitions. It shows that complexity and evolutionary change are the key characteristics of a market economy, not the equilibrium between supply and demand. First principles logic leads to very different conclusions about the economy than arise from both reasoning by analogy ("a government is just like a household"), and from accepting conventional "Neoclassical" economics: Private bank lending is more dangerous to economic stability than government spending; Attempts to reduce government debt in the past have actually led to financial crises like the GFC; and The Global Financial Crisis was caused by a private debt bubble which collapsed in 2007.
Kniha respektovaného ekonoma představuje makroekonomii zcela od základů prostřednictvím logiky „first principles“, obvykle používané v inženýrství. Autor krok za krokem vysvětluje podstatu peněz, mechanismus jejich tvorby a makroekonomické vztahy na základě účetních identit, nikoli tradičních neoklasických předpokladů. Ukazuje, že kapitalistická ekonomika je dynamický a evoluční systém, nikoli stav rovnováhy nabídky a poptávky. Na příkladech demonstruje, proč je soukromé zadlužování pro ekonomickou stabilitu nebezpečnější než vládní výdaje a jak se historické snahy o snižování veřejného dluhu podílely na vzniku finančních krizí, včetně globální krize v roce 2007–2008.
Obsahuje bibliografické odkazy
Keywords: makroekonomie; makroekonomická analýza; peníze; veřejný dluh; finanční krize; finanční inženýrství; monografie; macroeconomics; macroeconomic analysis; money; public debts; financial crises; financial engineering; monographs